Inhibition of soluble epoxide hydrolase increases coronary perfusion in mice. Issue 6 (15th June 2015) - Qin, Jun; Sun, Dong; Jiang, Houli; Kandhi, Sharath; Froogh, Ghezal; Hwang, Sung Hee; Hammock, Bruce D.; Wolin, Michael S.; Thompson, Carl I.; Hintze, Thomas H.; Huang, An
Abstract Roles of soluble epoxide hydrolase (sEH), the enzyme responsible for hydrolysis of epoxyeicosatrienoic acids (EETs) to their diols (DHETs), in the coronary circulation and cardiac function remain unknown. We tested the hypothesis that compromising EET hydrolysis/degradation, via sEH deficiency, lowers the coronary resistance to promote cardiac perfusion and function. Hearts were isolated from wild type (WT), sEH knockout (KO) mice and WT mice chronically treated with t‐TUCB (sEH inhibitor), and perfused with constant flow at different pre‐loads. Compared to WT controls, sEH‐deficient hearts required significantly greater basal coronary flow to maintain the perfusion pressure at 100 mmHg and exhibited a greater reduction in vascular resistance during tension‐induced heart work, implying a better coronary perfusion during cardiac performance. Cardiac contractility, characterized by developed tension in response to changes in preload, was potentially increased in sEH‐KO hearts, manifested by an enlarged magnitude at each step‐wise increase in end‐diastolic to peak‐systolic tension. 14, 15‐EEZE (EET antagonist) prevented the adaptation of coronary circulation in sEH null hearts whereas responses in WT hearts were sensitive to the inhibition of NO. Cardiac expression of EET synthases (CYP2J2/2C29) was comparable in both genotypic mice whereas, levels of 14, 15‐, 11, 12‐ and 8, 9‐EETs were significantly higher in sEH‐KO hearts, accompanied with lower levels of DHETs. In conclusion, the elevation of cardiac EETs, as a function of sEH deficiency, plays key roles in the adaptation of coronary flow and cardiac function.